2018
DOI: 10.1155/2018/5909827
|View full text |Cite
|
Sign up to set email alerts
|

The CLASS Surgical Site Characteristics in a Clinical Grading Scale and Anterior Segment Optical Coherence Tomography: A One-Year Follow-Up

Abstract: Purpose We combined a clinical grading scale and swept source anterior segment OCT to describe the successful and failed CLASS. Material and Methods 23 patients in the successful group and 17 patients in the failed group were compared in terms of the IBAGS grades and AS-OCT findings at one, three, and twelve months postoperatively. Results The majority in the successful group presented shallow blebs (91%, 57%, and 52% at 1M, 3M, and 12M, resp.). 59% of the failed group presented no bleb (H0 E0) from the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In addition, there was no significant correlation between the scleral pool size by UBM and the IOP after surgery. Similar results were determined in the studies by 36). This indicates that the drop in IOP may not depend on the size and shape of the scleral cistern; on the contrary, the presence of the scleral cistern is very important for IOP reduction.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, there was no significant correlation between the scleral pool size by UBM and the IOP after surgery. Similar results were determined in the studies by 36). This indicates that the drop in IOP may not depend on the size and shape of the scleral cistern; on the contrary, the presence of the scleral cistern is very important for IOP reduction.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we noticed that the bleb blood vessels in the surgical area showed mild or moderate congestion 1 month after surgery, which might be associated with postoperative inflammatory responses, stimulation by postoperative eye drops, or filtration route scarring. Jankowska-Szmul and Wylegala 5 also found that patients in the successful group after CLASS all exhibited mild vasculature (V2). However, interestingly, nobody in the successful group showed moderate vasculature (V3), but V3 was present in all failed patients in the early stage after CLASS.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, larger blebs were correlated with lower IOP. Jankowska-Szmul and Wylegala 5 observed bleb morphology after CLASS. One month after surgery, the majority of patients in the successful group presented diffuse blebs and had an H1 percentage of 91%, whereas the majority of patients in the failed group presented no blebs and had an H0E0 percentage of 59%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations